Step-by-step explanation:
In order to get the inverse of equation, we will interchange the variables and solve for x and y as follows.
![y = 2x^{2} - 8](https://tex.z-dn.net/?f=y%20%3D%202x%5E%7B2%7D%20-%208)
whereas, ![y + 8 = 2x^{2}](https://tex.z-dn.net/?f=y%20%2B%208%20%3D%202x%5E%7B2%7D)
or x = ![\sqrt{\frac{y+8}{2}}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7By%2B8%7D%7B2%7D%7D)
Now, on interchanging the variable we will get the equation as follows.
![x = 2y^{2} - 8](https://tex.z-dn.net/?f=x%20%3D%202y%5E%7B2%7D%20-%208)
![x + 8 = 2y^{2}](https://tex.z-dn.net/?f=x%20%2B%208%20%3D%202y%5E%7B2%7D)
y = ![\sqrt{\frac{x+8}{2}}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7Bx%2B8%7D%7B2%7D%7D)
The percentage of that ratio is 16%
The simplest way to find any percentage is to divide the numerator by the denominator.
in this case that would be 8/15=0.16
16/100=16%
First one is -8.
Second one, I can't tell because I don't see it
Answer:
14
Step-by-step explanation:
Since S is the midpoint of RT, then RS = ST
RS = RT - ST = (3x + 7) - (x + 7) = 3x + 7 - x - 7 = 2x
so we get that RS = 2x
but since RS = ST, and RS=2x & ST=x+7
then 2x = x + 7
2x-x = 7
x = 7
ST = x+7 = 7+7 = 14
P.S. Hope it makes sense. If you have any questions, feel free to ask them in the comments senction. I'll be happy to help. Have a wonderful day!
Answer:
D
Step-by-step explanation:
Z is the only relation that does not pass the vertical line test, so Z is not a function.
Answer: D